2021
DOI: 10.1101/2021.03.05.21252995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autologous cardiac micrografts as support therapy to coronary artery bypass surgery

Abstract: Objectives Cardio-regenerative cell therapies offer additional biologic support to coronary artery bypass surgery (CABG) for treating the myocardium suffering from or damaged by ischemia. This phase 1, open-label study assessed the safety and feasibility of epicardial transplantation of atrial appendage micrografts (AAMs) in patients undergoing CABG surgery. Methods Twelve consecutive patients destined for CABG surgery were included in the study. Six patients received AAMs during their operation and six patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similar therapy utilizing a small piece of the RAA has already been evaluated in conjunction with coronary artery bypass grafting (CABG) surgeries (9,11). With increased amounts of tissue, for example from the LAA, available for processing, larger areas can be treated, and increased doses can be administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar therapy utilizing a small piece of the RAA has already been evaluated in conjunction with coronary artery bypass grafting (CABG) surgeries (9,11). With increased amounts of tissue, for example from the LAA, available for processing, larger areas can be treated, and increased doses can be administered.…”
Section: Discussionmentioning
confidence: 99%
“…During LVAD implantation surgery, autologous cardiac tissue can be harvested for the purpose of cell therapy generation from, for example, atrial appendages and left ventricular tissue. Recent data have shown that epicardial transplantation of autologous right atrial appendage (RAA) micrografts is clinically safe and feasible and is associated with beneficial structural and functional effects on ischemic myocardium (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such follow-up of the IHD cohorts (STEMI I and CABG II) can be expected to provide biomarkers with prognostic properties. Moreover, the ability of epitranscriptomics-based blood biomarkers to reflect the responses to both current and novel cardiovascular therapies may extend their clinical applicability even further [ 114 , 115 , 173 ].…”
Section: Discussionmentioning
confidence: 99%